Damage mechanism of gamma-irradiated repurposed pultruded glass fibre polyester composite subjected to low-velocity impact using non-destructive techniques - Muhammad Imran Najeeb; Muhammad Amir Siti Madiha; Agusril Syamsir; Mohd Supian Abu Bakar; Sapizah Rahim; Asyraf Arif Abu Bakar; Tabrej Khan (Defence Technology)
Investigating the influence of radiation on glass fibre composites is essential for their use in space and aerospace environment. Gaining insight into the damage mechanisms caused by gamma irradiation, can improve the safety and resilience of structures. This paper is aimed at investigating the failure mode and damage of gamma-irradiated repurposed pultruded glass fibre-reinforced polyester subjected to low-velocity impact using three types of non-destructive techniques. Three sets of differently layered configurations (CRC, WCRW, W2CR2C) consisting of chopped (c), roving (r), and weaved (w) fibre-reinforced polyester are applied in this study. Drop hammer test is applied to evaluate the low-impact resistance properties of Gamma-irradiated composite at 100 kGy, 500 kGy, and 1000 kGy. Preliminary flexural and hardness tests are conducted to further assess the behaviour of irradiated polymer composites. Further, the damage modes associated with the low-impact test are characterised using infrared thermography, flat panel digital radiography, and microscope observation. The results show that the composites irradiated with various doses display good impact resistance at 20 J, presenting minor damages in the form of dents on the surface. The irradiated CRC and WCRW display best impact resistance at 500 kGy, while W2CR2C at 1000 kGy. This shows that the layering sequence of reinforcement fibre can influence the impact resistance of irradiated composites. Apart from that, the application of non-destructive techniques show different damage mechanisms in the form resin cracks, yarn splitting/fracture, and matrix splitting when the composites are exposed at high and low irradiation doses. These findings offer valuable data for the defence industry, particularly in the areas of repair, maintenance, and the development of new materials.